Analisis Beberapa Variabel Yang Berpengaruh Terhadap Pendapatan Penduduk Miskin Di Tiga Kabupaten Provinsi Bali - Dewi, Frisca Diana; Ayuningsasi, Anak Agung Ketut; Marhaeni, Anak Agung Istri Ngurah (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 8, No. 5, Mei 2019, pp (945-1180), 2019)
The problem of poverty is a problem that seems never lost in the world. Karangasem, Klungkung, and Buleleng regencies are the three regencies with the highest poor population in Bali Province. This study aims to analyze the influence of age, education, number of dependents, and working hours simultaneously and partially on the per capita income of the poor, and to analyze the dominant variables affecting the per capita income of the poor in Karangasem, Klungkung, and Buleleng regencies. The sample in this study amounted to 73 respondents. The analysis technique of this study uses multiple linear regression analysis. The results showed that age, education, number of dependents, and working hours simultaneously had a significant effect on per capita income of the poor in Karangasem, Klungkung, and Buleleng regencies and partially the variables of age, education, and working hours had a positive and significant effect, while the number of dependents does not affect the per capita income of the poor in the regencies of Karangasem, Klungkung, and Buleleng, and the dominant variable affecting the per capita income of the poor is the education variable. The government is expected to pay attention to the development of access to health and education. Keywords : age, education, number of dependents, working hours, income